Legal Analysis of Lavish Wedding Ceremonies from the Perspective of Islamic Law - Muhammad Yakhsyallah Liddinillah (Indonesian Journal of Law and Syariah, 2025)
This study aims to conduct an in-depth examination of the Islamic legal perspective on the increasingly prevalent practice of lavish wedding ceremonies in contemporary society. Employing a qualitative approach, the research analyzes primary Islamic sources such as the Qur’an and Hadith, as well as secondary sources including classical jurisprudential texts and scholarly interpretations. The objective is to assess the extent to which extravagant wedding practices align with the fundamental principles of Islamic law (sharia). The findings indicate a tension between the concept of lavish weddings and the Islamic values of modesty, justice, and the prohibition of wastefulness. The concepts of tabarruj (excessive display) and israf (extravagance), which are prohibited in Islam, can serve as a basis for analyzing excessive wedding reception practices. The study concludes that Islam promotes weddings that are simple, blessed, and free from financial and social burdens. The implications of this study are expected to contribute to a more comprehensive understanding of Islamic marital ethics and serve as a reference for Muslims in planning weddings that are consistent with religious teachings.